Validation of a two-dimensional educational software for the learning process of the design of Removable Partial Dentures - Watanabe, Romel (2023)
Objective: The objective of this study was to develop and implement a two-dimensional educational software for the learning process of designing Removable Partial Prostheses. Materials and Methods: The scientific method and educational evaluation procedures were utilized to address the needs of the Removable Partial Prosthesis subject in the Faculty of Dentistry at the UNMSM in Peru in 2022. Analysis, synthesis, and surveys were used. The software's applicability and fulfillment of teaching and learning requirements were examined, not only at the UNMSM but also in any university with similar requirements and characteristics. Results: The internal application of the software yielded a final value of 96%, while the evaluation of students and teachers showed a 90% acceptance rate, considering that SEDUPPR is simple to install, easy to use and operate, and is very useful for learn PPR design. Conclusion: The two-dimensional educational software designed for the learning process of Removable Partial Prosthesis is applicable and can be implemented in different educational settings.